Effect of Emission Penalty and Annual Interest Rate on Cogeneration of Electricity, Heat, and Hydrogen in Karachi: 3E Assessment and Sensitivity Analysis - Mehdi Jahangiri; Ali Mostafaeipour; Habib Ur Rahman Habib; Hamed Saghaei; Asad Waqar (Journal of Engineering)
Pakistan is the world’s sixth-most populous country with a semi-industrialized economy. It has been always an energy importer and dependent on fossil fuels. Great pressure is imposed on Pakistan’s national grid from the rise in fossil fuel costs, variations in the annual interest rate, and increased costs of greenhouse emissions. To meet the ever-increasing energy demand, the Government of Pakistan has decided to further harness wind and solar energies currently having a negligible share in Pakistan’s energy portfolio. Despite the importance of this issue, no study has been conducted so far on the cogeneration of power, heat, and hydrogen in Pakistan. Accordingly, this study is aimed at technical–economic–environmental sensitivity analysis of supplying electric and thermal loads of a residential building in Karachi by an off-grid wind-solar-fuel cell system. To this end, 4500000 possible cases were analyzed, simulated, and optimized with the HOMER software using 20-year average meteorological data from the NASA website. A sensitivity analysis was performed on this system for the first time in Pakistan. The other novelties are the use of dump loads for converting the surplus electricity into heat and also heat recovering in the fuel cells. The results showed the great potential of the station understudy for supplying the required power and heat by renewable energies. Hydrogen production was also affordable at every emission penalty price with an interest rate of less than 9%. Moreover, dump loads play a key role in supplying the thermal demand. Comparison of the wind turbine–solar cell–fuel cell–battery system with the wind turbine–solar cell–battery and solar cell–battery systems indicated that the internal rate of return and the payback period were, respectively, 9.39% and 11.4 years and 11.7% and 11 years. According to these results, it is recommend that Pakistani authorities promote the use of renewable energies through incentives and investment subsidies.